Contact geometry and electronic transport properties of Ag-benzene-Ag molecular junctions - SANVITO, STEFANO (My University, 2012)
The contact geometry and the electronic transport properties of Ag-benzene-Ag molecular junctions have been investigated by using first-principles quantum transport simulations. Our calculations show that a moderate benzene-silver interaction can be achieved when benzene is adsorbed on the Ag(111) surface through adatoms. In this case three symmetric Ag-benzene-Ag junction models can be constructed, in which the molecule is connected to the electrodes through one or two Ag adatoms on each side. Although the contribution to the transmission around the Fermi level made by benzene molecular orbitals depends on the number of Ag adatoms and the detailed binding configuration, the transmission coefficients at the Fermi level of the three junctions are calculated to be respectively 0.20, 0.18 and 0.16. These values are well consistent with the experimental one of 0.24?0.08. Our results thus demonstrate that the conductance of Ag-benzene-Ag junctions is rather stable regardless of the molecule/electrode contact geometry.
IN_PRESS
Keywords: Physical Chemistry; Molecular junctions; contact geometry; benzene-silver interactions; Nanoscience & Materials